Surface morphology of single crystal CuAlNi shape memory alloy - Wu, Jing Ai. (2008)
This dissertation investigates the variation of the surface roughness of a single crystal CuAINi SMA at different strains, and the surface topography at a certain strain when the surface is of good pattern. It may provide a very useful guide for the design of SMA based micro optical devices.